PEMBANGUNAN UNTUK KESEJAHTERAAN MASYARAKAT DI KAWASAN PESISIR - Teja, Mohammad (Jurnal Aspirasi, 2015)
Indonesia still has some wasted land. With the utilization of existing natural resources, sustainable communities through empowerment is expected to use the land to improve their welfare as well as environmental sustainability guard. Natural resources wisely utilized by the local community is expected to crushing poverty that has long fallen on them. The data used in this article come from secondary data, journals and the results of published studies and using literature methods. Community empowerment through improving the quality of education and knowledge should be encouraged by the central government, local government and investors. Through the cooperation, the local community is expected to be able to participate and play a role in the development of the area.